PENDIDIKAN ISLAM DI SINGAPURA - Rabiatul Adawiah (Cross-border, 2018)
The early history of the emergence of Islamic education in Singapore is said to have developed since the beginning of the arrival of Islam to Singapore itself. Islamic education in Singapore is delivered by scholars who come from other countries in Southeast Asia or countries in West Asia and from the small continent of India.